Existence and Uniqueness Results for a Class of Fractional Integro-Stochastic Differential Equations - Ayed. R. A. Alanzi; Shokrya S. Alshqaq; Raouf Fakhfakh; Abdellatif Ben Makhlouf (Fractal and Fractional)
The objective of this paper is to demonstrate the existence and uniqueness (EU) of solutions to a class of Fractional Integro-Stochastic Differential Equations (FISDEs) by utilizing the fixed-point technique (FPT) and stochastic techniques. Additionally, the paper proves the continuous dependence (CD) of solutions on the initial data. We examine the Hyers–Ulam stability (HUS) of FISDEs by applying Gronwall inequalities. Two theoretical examples are presented to demonstrate our findings.